2010
DOI: 10.3138/cjwl.22.1.169
|View full text |Cite
|
Sign up to set email alerts
|

A Feminist Perspective on Carbon Taxes

Abstract: Il y a un besoin urgent d'adopter des politiques canadiennes efficaces pour contrer le changement climatique. On consacre beaucoup d'énergie au choix et à la conception d'instruments de politique optimale et les questions d'efficacité environnementale et d'efficience économique dominent le débat. Il est néanmoins tout aussi important d'analyser comment ces politiques vont agir sur différents segments de la société et de s'assurer qu'elles soient conçues de manière juste afin de ne pas aggraver les inégalités s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…There is a similar silence about gender differentiated effects of climate mitigation policies in the North. Nathalie Chalifour considered the gendered effect of carbon taxes . She observed that carbon taxes are regressive, that is, because carbon taxes aim to increase the costs of carbon‐intensive goods and services that are essential to most households (e.g., transport, heating, and electricity) they disproportionately affect low income households.…”
Section: Climate Governance: Underrepresentation Silences and Gendementioning
confidence: 99%
See 1 more Smart Citation
“…There is a similar silence about gender differentiated effects of climate mitigation policies in the North. Nathalie Chalifour considered the gendered effect of carbon taxes . She observed that carbon taxes are regressive, that is, because carbon taxes aim to increase the costs of carbon‐intensive goods and services that are essential to most households (e.g., transport, heating, and electricity) they disproportionately affect low income households.…”
Section: Climate Governance: Underrepresentation Silences and Gendementioning
confidence: 99%
“…Nathalie Chalifour considered the gendered effect of carbon taxes. 58 She observed that carbon taxes are regressive, that is, because carbon taxes aim to increase the costs of carbon-intensive goods and services that are essential to most households (e.g., transport, heating, and electricity) they disproportionately affect low income households. Because women are overrepresented in low-income households, they carry a larger carbon cost burden compared to men.…”
Section: Climate Governance: Underrepresentation Silences and Gendementioning
confidence: 99%
“…Intersecting inequalities may exacerbate this problem: although women and people of color are disproportionately affected by climate change, and so have reason to mobilize for climate action, they also tend to be disproportionately vulnerable to the inflationary effects of carbon-centric mitigation policies. [87][88][89] More detrimentally to the cause of climate action, carboncentric policies sometimes provoke active counter-mobilization. Understanding anti-climate backlash requires attention to intersecting grievances, of which spatial inequalities are perhaps the most salient and tractable.…”
Section: Trepidation: the Politics Of Economic Insecuritymentioning
confidence: 99%
“…322 Langevin continues to put her hopes in the transformative character of GBA and calls for the introduction of a law that would make GBA mandatory. 323 Stephanie Paterson, however, doubts the utility and effectiveness of analytic, (Elson 1994;Bakker 1994;Keeble/Smith 1999;Biasutti n.d.;Fudge/ Vosko 2001;Grant 2002;Burke 2001;Tudiver 2002;Sjolander/Smith 2003;Elson 2003;Boyd 2003;Donner 2003;Tudiver/Valdés 2004;Carney 2004;Tudiver/Kammermayer 2005;Hankivsky 2005b;Spitzer 2005;Forget et al 2005;Doucet 2005;Paquette et al 2006;Bakker 2006;Boscoe/Tudiver 2007;Wolski 2007a;Morgan 2007;Boucher 2007;Spitzer/ Canadian Institutes of Health Research 2007;Nelson/Craggs 2007;Smith 2008;Yalnizyan 2008;Lahey 2009Lahey /2010Lahey 2010;Chalifour 2010;Drolet 2011;Pal 2001). For an ecofeminist, not GBA, analysis see (McLeod-Kilmurray 2008).…”
Section: 32 Implementation Of Gender Analysismentioning
confidence: 99%